RANCANG BANGUN APLIKASI PEMANDU WISATA DANAU TOBA BERBASIS WEB MENGGUNAKAN METODE AGILE - Rajagukguk, Chiki Stelys; Hutabri, Ellbert (LPPM Universitas Putera Batam, 2021)
ABSTRACT Lake Toba is the largest lake in Indonesia and the largest volcanic lake in the world, which is currently one of the tourist destinations in North Sumatra. Lake Toba has many tourist objects that are very beautiful and unspoiled, which will give satisfaction to every visitor. However, due to the lack of application of information technology, it often limits the number of tourists who will visit. This research was made to make it easier for tourists when visiting Lake Toba by creating an application to guide tourists when traveling on Lake Toba. Researchers make a web-based application, using the Agile method as a system development and using mysql as a database in order to further increase tourist satisfaction using the application. The results of this study are the application of a Lake Toba tour guide that will provide convenience and satisfaction in traveling on Lake Toba. This application will provide instructions for every tourist spot on Lake Toba, complete with routes to access these attractions. Application users can also provide ratings of attractions that have been visited, along with comments about experiences or suggestions for attractions. This application will also display the estimated fare to enter tourist destinations and transportation that will be used by tourists. This application will be accessible if connected to the internet network.